PUBLIC-PRIVATE PARTNERSHIP SEBAGAI SOLUSI PEMBANGUNAN INFRASTRUKTUR: STUDI LITERATUR PROYEK BANDARA KEDIRI - Alviana Ramadhani; Moh. Musleh; M. Husni Tamrin; Agus Subianto (Journal of Contemporary Public Administration, 2025)
Quality and sustainable infrastructure development is a major challenge for developing countries like Indonesia, especially in the face of budget constraints and administrative capabilities. The Public-Private Partnership (PPP) approach has emerged as a strategic solution to overcome these obstacles by involving the private sector in providing resources, technical expertise, and operational efficiency. This study aims to apply the PPP model in infrastructure development in Indonesia with a focus on the Kediri Airport project as a case study. The methodology used is an in-depth literature study of secondary data related to this project, including government policies, financing schemes, and technical implementation. The Kediri Airport project is an example of the first PPP (Government and Business Entity Cooperation) initiated by a business entity (unsolicited), with a Design-Build-Finance-Operate-Maintain-Transfer (DBFOMT) scheme. This project is fully funded by PT Gudang Garam Tbk through its subsidiary without using the APBN, with a total investment reaching IDR 10.8 trillion. The results of the study show that the PPP approach allows for accelerated infrastructure development while reducing the government's financial burden. Kediri Airport successfully operated in April 2024 with an initial capacity of 1.5 million passengers per year and is designed to support wide-body aircraft such as the Boeing 777-300ER. The novelty of this research lies in the analysis of the unsolicited PPP model that has not been widely implemented in Indonesia and the potential of this project as a catalyst for regional economic development. These findings provide strategic insights for the development of PPP models in the future, especially in large-scale projects that focus on curiosity.